The Leadership Model of Customary Village Based On Gender Equality - Sugiantari, Anak Agung Putu Wiwik; Anom, I Gusti Ngurah; Apriliani, Kadek; Unzila, Sandy Annisa; Widiani, Gusti Ayu Eka (Faculty of Law, Universitas Pekalongan, 2024)
The leadership of Balinese customary village is highly patriarchal so the position of the women in the leadership system is merely a subordinate of the man. It is an issue since the leadership development of the modern era does not discriminate against gender. This discrimination leads this study to formulate a new concept concerning leadership in customary villages based on gender equality. This study used the social-legal method. An interdisciplinary study is a hybrid of a grand study concerning the jurisprudence and science of law from a societal perspective. This study formulated a customary village leadership based ongender equality. This formulation was formed by implementing functions of the customary village comprehensively in form of the Woman Association (Pakis) as a new organization which empowers Balinese women. Pakis should make programs to empower and develop leadership for Balinese women, especially in the customary village leadership. Besides that, the nyentana marriage system that transforms the role of purusa (man) to be predana (woman) must be implemented comprehensively in Banjar so the woman who conducts this marriage system takes the position as a man and her name is listed in Banjar. The final formulation is by duplicating the leadership pattern in sekeha teruna teruni which has concerned with gender equality.